(untitled) (The International Journal for Scientific Research, 2026)
This study aimed to identify the adoption level of the Blue Ocean Strategy at the International University across its four dimensions (Elimination, Reduction, Raising, and Innovation) and to measure its impact on achieving competitive advantage through its dimensions (Cost, Flexibility, Quality, and Creativity). Additionally, the study explored the mediating role of the work environment in enhancing this relationship. The study employed a descriptive-analytical approach, utilizing a questionnaire as the primary tool for data collection from a stratified random sample. The results revealed that Innovation ranked first in terms of application level, followed by Raising and Reduction, while Elimination ranked last. Regarding competitive advantage, Quality achieved the first rank, followed by Creativity and Flexibility, with Cost ranking last. The findings indicated a significant direct positive effect of the Blue Ocean Strategy on competitive advantage, as well as a significant indirect positive effect through the work environment as a mediating variable. This highlights the critical importance of fostering the university’s internal climate to maximize strategic returns and achieve sustainable competitive excellence.